The Acquisition of Japanese Binding Form, Zibun by English-Speaking Children - SHIRAHATA, Tomohiko (Second Language, 2002)
This paper examines the relationship between the acquisition of subject-orientation (SO) and long-distance (LD) binding of the Japanese anaphor zibun (“self”) by English-speaking children acquiring Japanese as a second language (L2). These factors address the learnability problem of L2 acquisition. Zibun allows LD binding as well as local binding, which means that zibun does not always take its antecedent within its relevant local domain. Another property of zibun is that it is a subject-oriented anaphor, which requires the antecedent of zibun to be a subject. In contrast, the English anaphoric forms, such as himself do not allow LD binding and are not subject-oriented. Thus, if the initial state of an L2 learner's Japanese is influenced by his Ll (English), and he has access only to positive evidence, he will acquire LD binding in zibun with little difficulty, but he will have trouble acquiring [+SO] in zibun , because some form of evidence is needed to tell him that [-SO] is not allowed for zibun . This paper addresses this issue based on longitudinally collected L2 data from 12 English native-speaking children living in Japan. The results show that the L2 Japanese learners resemble L1 learners of Japanese in their acquisition of zibun despite the fact that they have already acquired English as an L1. One possible explanation for the absence of L1 influence is that the L2 learners fail to associate the L2 form zibun with corresponding reflexives in the L1 because they exhibit very different grammatical behaviors. Consequently, L2 learners follow the same acquisition path that L1 learners do.